Detection of low PPM of volatile organic compounds using nanomaterial functionalized reduced graphene oxide sensor - Mohd Tombel, Nor Syahira; Mohamad Badaruddin, Siti Aishah; Md Yakin, Firzalaila Syarina; Mohd Zaki, Hasan Firdaus; Syono, Mohd Ismahadi (AIP Publishing, 2021)
per, Volatile organic compounds (VOCs) detection was demonstrated on reduced graphene oxide (RGO) as ensing material that was integrated on Ti/Pt interdigitated electrode (IDE) deposited on a SiO2/Si substrate. The RGO sensing layer has been functionalized with gold nanoparticles (Au-NPs) to enhance the sensitivity of the gas sensor. The detection of ppm level of VOC gases such as acetone, toluene and isoprene were performed at room temperature 30C and 40% relative humidity (RH), with low operating temperature and low power consumption. The slopes value for RGO sensor response against gradual increase of concentration of VOC gas showed decrement in the resistance reading. The functionalization RGO with Au have improve the sensitivity and selectivity of the sensor towards the targeted VOC gas. The bare RGO sensing layer has a sensitivity towards acetone and RGO-Au (30W 75s) sensitive towards toluene. Meanwhile isoprene has a good response on the sensing element of the bare RGO and RGO-Au (70W 15s). Hence, RGO s sensing elements have shown good responses towards low concentration of VOCs gas at room temperature and ambient humidity.